APOE genotype and cognition in healthy individuals at risk of Alzheimer's disease: A review. (July 2018) - O'Donoghue, M. Clare; Murphy, Susannah E.; Zamboni, Giovanna; Nobre, Anna C.; Mackay, Clare E.
Abstract: APOE-ε4 is best known as a risk factor for Alzheimer's disease (AD). Consequently, there is considerable research interest in understanding whether APOE-ε4 influences cognition in healthy adults. Despite a substantial literature reporting effects of APOE genotype on cognition, findings are inconsistent. In particular, it is challenging to separate whether cognitive deficits in APOE-ε4 carriers reflect the influence of prodromal dementia pathology ("prodromal hypothesis"), or a direct contribution of APOE genotype to individual differences ("phenotype hypothesis"). Variable methodology across studies further complicates the issue. These challenges have limited what can be learnt about the processes underlying cognitive ageing and dementia by studying the influence of APOE genotype on cognition. In this review, we focus on the two compatible neurobiological mechanisms by which APOE genotype may influence cognition in healthy adults (prodromal and phenotype). We summarise the behavioural evidence for the influence of APOE on cognition in non-demented adults and explore key methodological challenges for disentangling the cognitive effects of different neurobiological mechanisms of APOE. Evidence suggests that at least some APOE-ε4 cognitive deficits are due to early AD pathology, whilst sensitive measures of cognition are beginning to reveal subtle cognitive differences between APOE genotypes in mid-adulthood, prior to the onset of the AD prodromal period. We conclude with recommendations for future research to investigate the cognitive consequences of neurobiological processes affected by APOE and maximise the translational potential of this research.